SARS-CoV-2 interacts with renin-angiotensin system: impact on the central nervous system in elderly patients - Quarleri, Jorge Fabian (2022)
SARS-CoV-2 is a recently identified coronavirus that causes the current pandemic disease known as COVID-19. SARS-CoV-2 uses angiotensin-converting enzyme 2 (ACE2) as a receptor, suggesting that the initial steps of SARS-CoV-2 infection may have an impact on the renin-angiotensin system (RAS). Several processes are influenced by RAS in the brain. The neurological symptoms observed in COVID-19 patients, including reduced olfaction, meningitis, ischemic stroke, cerebral thrombosis, and delirium, could be associated with RAS imbalance. In this review, we focus on the potential role of disturbances in the RAS as a cause for central nervous system sequelae of SARS-CoV-2 infection in elderly patients.